(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article examines about main features of polysemantic words in the Uzbek and English languages. To communicate and establish relationship with other, people use language as tool of communication Human beings are free to express their ideas, it means that they have the ability to transfer ideas from one person to the others. The function of language is not only as a tool of communication but also as a tool to persuade and influence people to do something.